On the street where you live - Clark, Mary Higgins (Simon & Schuster, 2001)
Feeling a need for stability after her divorce and pursuit by a stalker, criminal defense attorney Emily Graham accepts a job with a Manhattan law firm and buys the former family house in New Jersey. When the house is renovated, the corpse of a missing woman turns up along with evidence linked to a family disappearance in 1892.